Employing the references of Shariah Audit in supporting Governance of Iraqi Islamic Banks: An analytically study - ذنون الاء عبد الواحد (Journal of Economics and Administrative Sciences, 2018)
The Islamic Banks including the Iraqi ones are often resorted to support their governance frameworks in order to improve its competitiveness in their communities. Where, those banks are looking for activities that enhance their governance; one of these activities is Shariah Audit that provided the auditing capabilities to face of developmental challenges and increase competitiveness. Therefore, the content of this paper, discusses know-how to use the Shariah Audit and its references in support of the Shariah Governance in the Iraqi Islamic banks. The proposed hypothetical model was built to reflect this know-how through four hypotheses, which in turn were subject later to statistical analysis, such: Regression and Path Analyses using the (SPSS) software. In the concentration on eight Iraqi Islamic banks that described as a field laboratory for our paper, the data were collected using a questionnaire formed from (20) indicators in the context of five variables essential. Finally, the paper has reached several conclusions, the most important of which: the Iraqi Islamic banks believe that employing the Shariah Audit references in their work have a direct positive effect (focusing on the Shariah reference) and indirectly (with emphasis on synergy between the value reference and other references) to support their governance. In addition, the paper recommend the need to encourage academic institutions and professional organizations in order to pave the way for a rethinking of the drafting and construction of the Shariah Audit theories and concepts, which can describe as one of the developed areas of Audit and a cornerstone in the Islamic finance industry.